6 - Corruption, croissance et capital humain : quels rapports ? - Seka, Pierre Roche (Africa Development, 2021)
The objective of this paper is to explain some of the reasons of the high rate of dropout observed in the system of higher education in the African universities. It has been shown, theoretically, that corruption is one of the major factors. Indeed, very talented students, who otherwise could have pushed further their studies, suddenly dropout when they compare the level of wellbeing of those who are well educated with that of those who are not but enriched through corruption. Where do they go? They join the later in their corruptive activities. Such practice, that somehow is rational, endangers the whole education system. A simplified theory of bank panic has been used to show that whenever talented students are informed on how the bad student are enriched by corruption, they drop out to join the bad students. An econometric model has been estimated to show the negative impact of corruption on the registration rate for higher education. The paper ends by calling for the attention of the public authority that if nothing is done to retribute better well educated people, the education system is at high risk of extinction, endangering growth and development efforts that have been made so far.